Greenhouse Cucumber Production - Florida Greenhouse Vegetable Production Handbook, Vol 3 - Robert Hochmuth (EDIS)
This document outlines all the considerations to take into account when growing cucumbers in greenhouses. Greenhouse cucumber production is very popular in many areas of the world. The cucumber is a warm season crop with required growing conditions of 80°F to 85°F and plenty of sunlight. Traditionally the primary type of cucumber grown in Florida greenhouses is the standard European seedless type. The fruits are mild in flavor, seedless, and have a thin edible skin that requires no peeling. Harvested fruit generally range from 12 to 14 inches in length and weigh about 1 pound each. This text is one of the chapters of the Florida Greenhouse Vegetable Production Handbook. First published Dec. 1990.